Factors Contributing to Student Anxiety during Classroom Presentation: A Qualitative Study - Melisa Melisa; Darmawan Darmawan; Wahyudin Wahyudin; Mochtar Marhum (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
This study investigates the factors contributing to student anxiety during classroom presentations, particularly among fourth-semester students in the English Education Program at Tadulako University. Employing a qualitative descriptive design, the research involved questionnaires using the Foreign Language Classroom Anxiety Scale (FLCAS) and semi-structured interviews. The findings reveal that psychological factors (e.g., low self-confidence, fear of negative evaluation), social factors (peer and teacher pressure), and environmental conditions (e.g., formal settings, lack of preparation time) significantly contribute to students’ anxiety levels. The research underscores the need for supportive classroom environments, targeted teaching strategies, and regular feedback to help students manage presentation anxiety effectively. This paper contributes to the development of anxiety-reduction interventions that can enhance students' oral communication competence in academic settings.